ANALISIS SISTEM ANTRIAN PADA AREA FINAL INSPECTION DI VEHICLE LOGISTIC CENTER PT ADM UNTUK OPTIMALISASI JUMLAH SERVER, WAKTU TUNGGU, DAN TOTAL BIAYA PELAYANAN - Kamillie, Sonny; -, Jonny (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
Industry stakeholders are expected to work faster to fulfill market demands and avoid loss of opportunity in business. An effective and efficient system is need to support this expectation. This study examines the queueing system on Vehicle Logistic Center for optimalizing total number of servers. Long queues usually occur at the Final Inspection area. Data is collected and calculated, subsequently simulates using promodel 7.0. The result of this research shows that optimal total number of servers with a reduced waiting time of 11,60% and total cost of Rp 41.056,00.It is recommended that the company uses 2 (two) server for the queuing system in the Final Inspection area in order to improve service quality.